Business intelligence for sustainable competitive advantage - Ahmad, Azizah (Emerald Group Publishing Limited, 2015)
The strategic management literature emphasizes the concept of business intelligence (BI) as an essential competitive tool.Yet the sustainability of the firms’ competitive advantage provided by BI capability is not well researched.To fill this gap, this study attempts to develop a model for successful BI deployment and empirically examines the association between BI deployment and sustainable competitive advantage.Taking the telecommunications industry in Malaysia as a case example, the research particularly focuses on the influencing perceptions held by telecommunications decision makers and executives on factors that impact successful BI deployment.The research further investigates the relationship between successful BI deployment and sustainable competitive advantage of the telecommunications organizations.Another important aim of this study is to determine the effect of moderating factors such as organization culture, business strategy, and use of BI tools on BI deployment and the sustainability of firm’s competitive advantage. This research uses combination of resource-based theory and diffusion of innovation (DOI) theory to examine BI success and its relationship with firm’s sustainability.The research adopts the positivist paradigm and a two-phase sequential mixed method consisting of qualitative and quantitative approaches are employed.A tentative research model is developed first based on extensive literature review.The chapter presents a qualitative field study to fine tune the initial research model.Findings from the qualitative method are also used to develop measures and instruments for the next phase of quantitative method.The study includes a survey study with sample of business analysts and decision makers in telecommunications firms and is analyzed by partial least square-based structural equation modeling.The findings reveal that some internal resources of the organizations such as BI governance and the perceptions of BI’s characteristics influence the successful deployment of BI.Organizations that practice good BI governance with strong moral and financial support from upper management have an opportunity to realize the dream of having successful BI initiatives in place.The scope of BI governance includes providing sufficient support and commitment in BI funding and implementation, laying out proper BI infrastructure and staffing and establishing a corporate-wide policy and procedures regarding BI.The perceptions about the characteristics of BI such as its relative advantage, complexity, compatibility, and observability are also significant in ensuring BI success. The most important results of this study indicated that with BI successfully deployed, executives would use the knowledge provided for their necessary actions in sustaining the organizations’ competitive advantage in terms of economics, social, and environmental issues.This study contributes significantly to the existing literature that will assist future BI researchers especially in achieving sustainable competitive advantage.In particular, the model will help practitioners to consider the resources that they are likely to consider when deploying BI.Finally, the applications of this study can be extended through further adaptation in other industries and various geographic contexts.